New Methods and Ways of Foreign Language Teaching - Хikmatova Muqadas Nurilloevna (Genius Journals, 2021)
The article provides information on new methods of foreign language teaching, as well as ideas for new materials and methods used in foreign language teaching. In addition, these methods were analyzed using examples.
Keywords: New Methods; Foreign Language Teaching; New Materials; Methodology